Do changes in the real exchange rate affect the trade balance? Evidence from European countries - Felipe, Jesus (Animo Repository, 2024)
We use five time and frequency domain causality tests to study whether unit labor costs-based real exchange rate depreciations / appreciations caused improvements / deteriorations in the trade balances of ten Eurozone economies, and thus contributed to closing trade imbalances, during 1995-2019. The methods we use deal with the inherent nonlinearity, and structural shifts in the time series. They also take into account asymmetry and regime changes. The non-parametric approach avoids the possible bias associated to the identification strategy. Test results indicate that there is no evidence of such a causal relationship.